2014
DOI: 10.3109/0142159x.2014.886009
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate medical students’ perceptions on the quality of feedback received during clinical rotations

Abstract: Results demonstrate that feedback on students' clinical performance is often not forthcoming and when offered it is deficient and fails to concentrate on the development of different clinical skills. This highlights the critical challenges that need to be addressed by teachers, medical education unit and all hospital departments in order to enhance giving effective and structured feedback to medical students during clerkships. Results also raise the extreme need for the establishment and enhancement of a cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 22 publications
3
23
0
3
Order By: Relevance
“…[ 8 ] Feedback highlights the critical challenges that need to be focused by the faculty and medical education unit. [ 9 ] Many studies have shown that if education is research oriented and field based, students will not only gain knowledge but also learn the clinical skills and research methodology. [ 10 11 ] During the re-orientation of medical education (ROME)[ 12 13 14 15 ] posting of undergraduate medical students in the Department of Community Medicine, a field-based activity was planned and data were collected by the students using a smartphone app under the guidance of faculty and postgraduate students.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Feedback highlights the critical challenges that need to be focused by the faculty and medical education unit. [ 9 ] Many studies have shown that if education is research oriented and field based, students will not only gain knowledge but also learn the clinical skills and research methodology. [ 10 11 ] During the re-orientation of medical education (ROME)[ 12 13 14 15 ] posting of undergraduate medical students in the Department of Community Medicine, a field-based activity was planned and data were collected by the students using a smartphone app under the guidance of faculty and postgraduate students.…”
Section: Introductionmentioning
confidence: 99%
“…13 Despite the importance of feedback for facilitating improvements in SRL, students perceive the effectiveness of feedback in academic and clinical contexts to be poor. [14][15][16] What remains unclear is whether these perceptions relate to feedback at the level of the task (i.e. what students got wrong at assessment), or whether they relate to feedback about aspects of SRL (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire was developed from the literature available and modified to match the local situation after being piloted on a group of students and the faculty [ 12 ]. The items in the questionnaire form obeyed Likert-type rating scales in which the respondent is asked to show the level of agreement or disagreement according to five-point Likert scale, where (1, strongly disagree; 5, strongly agree).…”
Section: Methodsmentioning
confidence: 99%